Bimbingan dan Konseling Islam dengan Terapi Behavior untuk Mengatasi Perilaku Maladatif Mahasiswa Thailand di Universitas Islam Negeri Sunan Ampel Surabaya (Jurnal Bimbingan dan Konseling Islam, 2017)
The purpose of this study is to know the process of Islamic guidance and counseling with behavioral therapy to address the students ' maladative behavior at Sunan Ampel State Islamic University Surabaya. In answering the problem, this research uses qualitative research method with comparative descriptive approach. While in the collection of data through observation, interviews, and documentation. The study uses live model techniques (real models) in which the Counselor invites the Consley to perform observations or observations on the model of physical appearance, interaction, friendliness, and a life of responsibility. The final outcome of the Islamic guidance and counseling process with behavioral therapy to address the students ' maladative behavior at the Sunan Ampel State Islamic University of Surabaya is said to be quite successful with the 83% procedural which the result is Can be seen from the change in conditions of Consley or attitude less well start guidance and counseling Islam with Behavior therapy to attribute more, that is, the process of adjusting the self-contemplated Consley can togeth the new environment after Get BKI with modeling techniques.